Metabolic profiling of prebiotic, probiotic, and synbiotic supplements in a canine colonic fermentation model: a pilot feasibility study reveals distinct and complementary effects - Gramenzi, Alessandro; Clerico, Luana; Belà, Benedetta; Di Leonardo, Meri; Fusaro, Isa; Pignataro, Giulia (Frontiers in Veterinary Science, 2025)
IntroductionThe gut microbiota is a central player in canine health, influencing digestion, immune modulation, and metabolic homeostasis. Microbiota imbalance fuels interest in dietary interventions such as prebiotics, probiotics, and synbiotics (a combination of prebiotics and probiotics).MethodsThis pilot feasibility study employed the SCIME™, a novel in vitro fermentation model simulating the canine colonic environment, to evaluate the metabolic effects of three dietary supplements using fecal inoculum from a single healthy canine donor. Products tested were Microbiotal (product M), a probiotic (product P, Lactobacilli reuteri), and a synbiotic (product M + P: Microbiotal +L. reuteri). Over a 2-week treatment period, fermentation parameters, including short-chain fatty acid (SCFA) production, acidification trends, and proteolytic activity, were measured using a high-resolution metabolomic profiling via the Laser-Assisted Rapid Evaporative Ionization Mass Spectrometry (LA-REIMS).ResultsDescriptive observations revealed distinct and complementary metabolic patterns. Microbiotal supplementation enhanced acidification in both the proximal and distal colon, with stimulation of acetate production in the proximal colon. Treatment with L. reuteri stimulated lactate production while reducing acetate and propionate levels. The synbiotic treatment showed combined effects, increasing acetate in the distal colon and producing metabolic shifts, as determined by LA-REIMS analysis. All treatments showed trends toward increased proteolytic markers in the distal colon.ConclusionThis pilot in vitro feasibility study demonstrates that prebiotics, probiotics, and synbiotics produce distinct metabolic fingerprints in vitro, warranting future validation through studies with multiple donors, independent SCIME™ runs, and in vivo trials to assess generalizability and explore potential applications in canine gastrointestinal research.